Analysis of Impact on Operating Characteristics of New Power System in Low-Temperature Weather - Zhipeng Liu; Yicong Wang; Yanling Lv (IEEE Access, 2025)
The secure operation of modern power systems is significantly compromised under low-temperature extreme weather conditions. This study investigates the operational characteristics of a novel power system under such conditions by integrating meteorological modeling with power system analysis. Specifically, the distinct features of two prevalent low-temperature weather patterns—cold waves and freezing rain—are incorporated into the system modeling framework. The proposed approach begins with a systematic analysis of meteorological characteristics and disaster-inducing factors, where the severity of these factors is employed to classify different weather scenarios. This classification enables the quantitative assessment of low-temperature impacts on power system components, particularly focusing on ice-induced generation loss in renewable energy systems and the increased failure probability of transmission lines due to ice accumulation. Subsequently, the operational behavior of power system equipment under extreme weather is simulated using a non-sequential Monte Carlo approach. To capture the dynamic topological changes caused by elevated line fault rates, graph-theoretic analysis and connected component identification techniques are applied. This leads to the development of a comprehensive power system model that accounts for both energy dynamics and structural reconfiguration. Key operational metrics, including voltage and system frequency, are evaluated through power flow analysis and primary frequency regulation. The proposed methodology is validated using the IEEE-RTS 79 test system, providing a quantitative assessment of power system performance under low-temperature weather.